Real-time cyber physical system testbed for power system security and control. (September 2017) - Poudel, Shiva; Ni, Zhen; Malla, Naresh
Highlights: A real-time cyber physical system testbed is developed based on OPAL-RT, SEL 351S protection system, high-performance computers and communication networks. The impact of a real-time cyber attack on the multimachine power system is studied in terms of voltage stability and generation loss. Two different mitigation strategies are studied offline using optimal power flow for system reconfiguration in order to restore normal or next steady state operating condition after failures. The ADP based real-time adaptive control is conducted for multimachine power system during the load fluctuations based on this proposed cyber physical system platform. Abstract: The existing electric power grid is upgraded into a smart grid through an intelligent communication infrastructures, layers of information, extensive computing and sensing technologies. These cyber and physical components of grid together constitute a complex cyber-physical system (CPS), and this integration increases the risk from cyber attacks and introduces new vulnerabilities to the power system. Researchers need a power system testbed which can provide a platform for realistic experiments. This paper presents the development of a real-time cyber-physical system testbed for cyber security and stability control. We use SEL 351S protection system with OPAL-RT including control functions and communications to build a cyber-physical environment. In this testbed, we conducted power grid security experiment by knocking down two transmission lines in a row and analyzed the impact of failures. Meanwhile, we provided two mitigation strategies for this failure using optimal power flow. In addition, we conducted load fluctuations for multimachine power system, and provide timely adaptive control strategies.